The Lived Experience of Chronic Hepatitis B: A Broader View of Its Impacts and Why We Need a Cure - Thomas Tu; Joan M. Block; Su Wang; Chari Cohen; Mark W. Douglas (Viruses, 2020)
Chronic hepatitis B (CHB) is one of the most widespread liver diseases in the world. It is currently incurable and can lead to liver cirrhosis and cancer. The considerable impacts on society caused by CHB through patient mortality, morbidity, and economic loss are well-recognised in the field. This is, however, a narrow view of the harms, given that people living with CHB can be asymptomatic for the majority of their life-long infection. Of less-appreciated importance are the psychosocial harms, which can continue throughout an affected person’s lifetime. Here we review the broad range of these impacts, which include fear and anxiety; financial loss and instability; stigma and discrimination; and rejection by society. Importantly, these directly affect patient diagnosis, management, and treatment. Further, we highlight the roles that the research community can play in taking these factors into account and mitigating them. In particular, the development of a cure for hepatitis B virus infection would alleviate many of the psychosocial impacts of CHB. We conclude that there should be a greater recognition of the full impacts associated with CHB to bring meaningful, effective, and deliverable results to the global community living with hepatitis B.